Analisis Penerapan Dana Alokasi Umum Spesific Grant (Dau-Sg) Pada Badan Keuangan dan Aset Daerah Kabupaten Gorontalo - Siti Rahmiati Ishak; Lufiah Irwan Radjak; Mentari Ariesta Iyonu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the implementation of the General Allocation Fund for Special Grants (DAU-SG) at the Regional Finance and Asset Agency (BKAD) of Gorontalo Regency. The background of this study is based on obstacles in the management of DAU-SG, such as delays in disbursement of funds, limited human resources, and less than optimal budget realization in the infrastructure sector. The novelty in this study lies in the implementation of the General Allocation Fund for Special Grants (DAU-SG) at the Regional Finance and Asset Agency of Gorontalo Regency using the policy implementation theory of Donald S. Van Meter & Carl E. Van Horn. This study uses a qualitative method with a case study approach, data collection is carried out through observation, interviews, and documentation involving 5 informants as sources. The results of the study indicate that the implementation of DAU-SG at BKAD of Gorontalo Regency based on the implementation theory of Donald S. Van Meter and Carl E. Van Horn there are several indicators that are still not optimal, such as understanding of policy goals and objectives that are not fully understood, the existence of imbalances in human resource work capacity. Social and economic conditions are favorable, but political dynamics still show a tug-of-war between interests, which poses obstacles to program implementation. Furthermore, what is optimal is good communication between stakeholders, implementation has received support from the central government, and leadership coordination is quite good.